Performance Assessment Comprehensively Based on Project Learning Related to Critical Thinking: A Bibliometric Analysis - Sudirman Sudirman; Aliefman Hakim; Hamidi Hamidi (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to find out a comprehensive performance assessment using project-based learning and improving critical thinking. The method of writing articles through literature studies published in 2010-2022 uses descriptive qualitative bibliometric analysis with the Perish 8 and VOSviewer applications, from 1000 articles sourced from journals, books, conferences, proceedings, and other literature sources that have been screened in the Google Scholar (GS) and Scopus databases with the Perish 8 application, researchers only take articles sourced from journals, namely 343 articles and only 1 09 articles are Scopus with 45 articles that are on quartile one (Q1), 34 articles on quartile two (Q2), 23 Articles at quartile level three (Q3) and 7 articles are at level quartile four (Q4) to be used as a reference for literature studies in conducting further article reviews. The results of the bibliometric analysis qualitatively found that there was a relationship between comprehensive performance assessment based on project-based learning and critical thinking.